A role for SETMAR in gene regulation: insights from structural analysis of the dna-binding domain in complex with dna - Chen, Qiujia (2016)
Indiana University-Purdue University Indianapolis (IUPUI) === SETMAR is a chimeric protein that originates from the fusion of a SET domain to the mariner Hsmar1 transposase. This fusion event occurred approximately 50 million years ago, after the split of an anthropoid primate ancestor from the prosimians. Thus, SETMAR is only expressed in anthropoid primates, such as humans, apes, and New World monkeys. Evolutionary sequence analyses have revealed that the DNA-binding domain, one of the two functional domains in the Hsmar1 transposase, has been subjected to a strong purifying selection. Consistent with these analyses, SETMAR retains robust binding specificity to its ancestral terminal inverted repeat (TIR) DNA. In the human genome, this TIR sequence is dispersed in over 1500 perfect or nearly perfect sites. Given that many DNA-binding domains of transcriptional regulators are derived from transposases, we hypothesized that SETMAR may play a role in gene regulation. In this thesis, we determined the crystal structures of the DNA-binding domain bound to both its ancestral TIR DNA and a variant TIR DNA sequence at 2.37 and 3.07 Å, respectively. Overall, the DNA-binding domain contains two helix-turn-helix (HTH) motifs linked by two AT-hook motifs and dimerizes through its HTH1 motif. In both complexes, minor groove interactions with the AT-hook motifs are similar, and major groove interactions with HTH1 involve a single residue. However, four residues from HTH2 participate in nucleobase-specific interactions with the TIR and only two with the variant DNA sequence. Despite these differences in nucleobase-specific interactions, the DNA-binding affinities of SETMAR to TIR or variant TIR differ by less than two-fold. From cell-based studies, we found that SETMAR represses firefly luciferase gene expression while the DNA-binding deficient mutant does not. A chromatin immunoprecipitation assay further confirms that SETMAR binds the TIR sequence in cells. Collectively, our studies suggest that SETMAR functions in gene regulation.